Efektifitas Asam Terhadap Kualitas Smoothies Campuran Pisang Ambon, Stroberi, Dan Biji Chia - Connie Daniela (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Innovations in fruit-based food technology have widespread with various health benefits, one of which is the form of smoothies. Smoothies are mixed drinks from fruits or vegetables added to yogurt, by grinding together, the benefits of which are used as alternative drink for people with hypertension. However, the problem is related to the shelf life of the smoothies, therefore is necessary to add food additives such as citric acid to increase shelf life of the smoothies. This study aims to determine the effect of adding citric acid as preservative in maintaining the shelf life of smoothies. The study was designed using factorial RAL with addition of citric acid concentration (2%,4%,6%,and8%) and storage time (1 day,3 days,5 days, and7days). The parameters tested were vitamin C levels, antioxidant levels, total dissolved solids, pH values, and taste organoleptic tests. Based on the results of study it was known that 8% citric acid treatment with 1 day storage time was the best treatment. The results obtained were parameter levels of vitamin C (35,225mg/100g), levels of antioxidants (82,335%), total dissolved solids (32,21oBrix), pH value (2,765), and taste organoleptic test (4,978 which means very favorable). Storage 3, 5, did not have significant effect on nutritional levels.